Upaya Meningkatkan Literasi Membaca dengan Media Flashcard pada Siswa Kelas 1 SD - Ismatun Nisak; Diana Shima Amrita; Syailin Nichla Choirin Attalina (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This classroom action research aims to improve the reading literacy of grade 1 students of SD Negeri 2 Ngasem through the use of flashcards. The background of the study is based on the low interest in reading and literacy outcomes of students, which is caused by less varied learning methods and the lack of attractive learning media. This study used a multi-cycle approach with the stages of planning, implementation, observation, and reflection. Data were collected through observation of student activities, reading literacy tests before and after the intervention, and documentation of the learning process. The results showed an increase in the average reading literacy score from 74.77 in the pre-cycle to 75.55 in cycle 1, with the percentage of learning completeness increasing from 77.77% to 83.33%. The use of flashcards proved effective in improving students' motivation, participation, and reading literacy outcomes. This study recommends the use of interactive and innovative learning media such as flashcards, to improve reading literacy in elementary schools.